TURN YOUR INDUSTRY UPSIDE DOWN. Issue 1 (March 2016) - Mullins, John; Ersek, Barret; Keller, Eileen Weisenbach
Abstract : Turn your industry upside‐down by flouting the rules, say LBS'sJohn Mullins and co‐authorsBarrett Ersek andEileen Weisenbach Keller